2014
DOI: 10.1007/s00417-014-2779-z
|View full text |Cite
|
Sign up to set email alerts
|

Structures affecting recovery of macular function in patients with age-related macular degeneration after intravitreal ranibizumab

Abstract: The macular function measured by the fmERGs was determined by the parafoveal outer layer and SRD thickness in patients with exudative AMD. Of these, changes in the SRD thickness by IVRs most strongly affected the recovery of macular function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Furthermore, the group free of SRD at 6 months showed better vision improvement than that with SRD, despite receiving fewer retreatments. Nishimura et al, [ 18 ] studying eyes with AMD treated with IVR, reported that SRD thickness correlated negatively with the a-wave amplitude on electroretinography. In other words, SRD has an important association with macular functions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the group free of SRD at 6 months showed better vision improvement than that with SRD, despite receiving fewer retreatments. Nishimura et al, [ 18 ] studying eyes with AMD treated with IVR, reported that SRD thickness correlated negatively with the a-wave amplitude on electroretinography. In other words, SRD has an important association with macular functions.…”
Section: Discussionmentioning
confidence: 99%